Improvement of Aerodynamic Performance of Bilaterally Symmetrical Airfoil by Co-Flow Jet and Adaptive Morphing Technology - Zeyu Lu; Hongming Cai (Aerospace)
For a special bilaterally symmetric airfoil (BSA), this paper designs an active flow control scheme based on the Co-Flow Jet (CFJ) and adaptive morphing technology, and establishes a numerical simulation method which is suitable for simulating aerodynamic characteristics. The accuracy and effectiveness of the numerical method has been verified through benchmark cases. This study investigates the effects of jet intensity, suction slot position and angle, and deflection angles of the leading and TE flap on the aerodynamic performance parameters and flow field structure of the bilaterally symmetric airfoil. The results show that the adaptive morphing technology can significantly improve the equivalent lift coefficient and equivalent lift-to-drag ratio of the bilaterally symmetric airfoil, without obviously increasing the CFJ power consumption coefficient. Selecting an appropriate CFJ intensity can achieve a relatively high equivalent lift-to-drag ratio with a low compressor power requirement. Moving the suction slot rearward can increase the lift coefficient, and placing it on the trailing edge (TE) flap can more efficiently delay flow separation, reduce power consumption, and increase the equivalent lift-to-drag ratio. The suction slot angle has little effect on the lift coefficient, but a larger suction slot angle can enhance the equivalent lift-to-drag ratio. Increasing the TE flap deflection angle enhances both the lift coefficient and drag coefficient, as well as the power consumption coefficient at high angles of attack. But it has little effect on the maximum equivalent lift-to-drag ratio. Increasing the leading edge flap deflection angle can improve the maximum equivalent lift-to-drag ratio while increasing the angle of attack corresponding to it. Overall, choosing a CFJ and adaptive morphing parameters by considering different factors can enhance the aerodynamic performance of the bilaterally symmetric airfoil.